2003
DOI: 10.1038/sj.bmt.1704038
|View full text |Cite
|
Sign up to set email alerts
|

Nonmyeloablative allogeneic hematopoietic stem cell transplantation for congenital sideroblastic anemia

Abstract: Congenital sideroblastic anemia (CSA) is a dyserythropoietic disorder that leads to transfusion dependency and subsequent iron overload. Nonmyeloablative allogeneic hematopoietic stem cell transplantation (NST) was performed for a patient with CSA, who had contraindications to conventional allografting. Conditioning was fludarabine, low-dose total body irradiation and antithymocyte globulin, followed by peripheral blood stem cell transplant. Cyclosporine and mycophenolate mofetil were used for graft-versus-hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
(11 reference statements)
0
11
0
Order By: Relevance
“…Owing to its role as amino acid carrier for mitochondria, it has been suggested that glycine supplement may ameliorate transfusion requirement in SLC25A38 -associated congenital sideroblastic anaemia. Bone marrow transplantation is the only cure for the disease 5 14 15. Therefore, genetic workup of congenital sideroblastic anaemia is essential for prediction of treatment response, enabling genetic counselling and prenatal diagnosis in future pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to its role as amino acid carrier for mitochondria, it has been suggested that glycine supplement may ameliorate transfusion requirement in SLC25A38 -associated congenital sideroblastic anaemia. Bone marrow transplantation is the only cure for the disease 5 14 15. Therefore, genetic workup of congenital sideroblastic anaemia is essential for prediction of treatment response, enabling genetic counselling and prenatal diagnosis in future pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Transfusion support and iron chelation therapy are indicated in this group of patients. Allogeneic stem cell transfusion may be curative but depends on availability of a suitable donor 5 14. It has been suggested that glycine may theoretically be helpful in alleviating the transfusion requirement5 14 15 and the patient was given glycine at 150 mg/kg/day for 6 months, but the frequency of transfusion remained the same.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the previously described six patients with CSA of undefined cause who were treated with HSCT, five received myeloablative conditioning with busulfan and cyclophosphamide +/− antithymocyte globulin (ATG) as the preparative regimen . One patient, who could not receive conventional myeloablative conditioning due to underlying comorbidities, received fludarabine, low‐dose total body irradiation, and ATG . Despite full engraftment, he succumbed to GVHD and prior iron overload on day +190.…”
Section: Discussionmentioning
confidence: 99%
“…For severe, transfusion‐dependent sideroblastic anemia, treatment with hematopoietic stem cell transplantation (HSCT) had been reported in the limited number of six cases with apparent CSA although their molecular basis was not known . More recently, a few anecdotal cases having identified molecular defects in SLC25A38 who were treated with HSCT were briefly annotated .…”
Section: Introductionmentioning
confidence: 99%